FISCAL ALLOCATION CHALLENGES: A STUDY OF CAPITAL EXPENDITURE IN ONDO STATE'S LOCAL GOVERNMENTS - Adeyemi, Michael Olufemi; Ojo, Esther Abimbola (Ayden Journal of Management and Social Sciences, 2024)
In the realm of public budgeting, the imperative of democratic participation in decision-making processes has been emphasized as a means to align government priorities with the needs and aspirations of the populace. Onimode (1999) advocates for democratic budgeting, wherein the involvement of citizens allows for a more representative allocation of resources. However, in practice, decision-making often remains concentrated in the hands of dominant individuals within and outside government, deviating from the ideal of participatory governance. The disconnect between public expectations and actual decision-making underscores the importance of efficient and effective resource utilization in fulfilling government responsibilities. Citizens rightly expect their government to utilize available resources judiciously to deliver optimal public services. To gauge the efficacy of government programs and allocate resources appropriately, the use of performance indicators becomes paramount. By measuring the efficiency and outcomes of program efforts, performance indicators serve as a tool for assessing government performance and communicating program objectives and effectiveness to the public. This abstract delves into the dichotomy between democratic ideals and practical governance realities in public budgeting, emphasizing the role of performance indicators in enhancing accountability and transparency. Drawing on insights from Onimode (1999), the abstract highlights the importance of citizen participation in budgetary processes and the need for effective mechanisms to measure and communicate government performance. Understanding these dynamics is crucial for fostering responsive and accountable governance that meets the expectations of citizens